The laboratory findings and different COVID-19 severities: a systematic review and meta-analysis - Erfan Kazemi; Reihane Soldoozi Nejat; Fatemeh Ashkan; Hossein Sheibani (BMC, 2021)
Abstract Background Abnormal laboratory findings are common in patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The aim of this systematic review was to investigate the effect of the level of some laboratory factors (C-reactive protein (CRP), creatinine, leukocyte count, hemoglobin, and platelet count) on the severity and outcome of coronavirus disease 2019 (COVID-19). Methods We searched PubMed, Web of Science, Scopus, and Google Scholar. We collected the articles published before May 26, 2020. We gathered the laboratory factors in groups of patients with COVID-19, and studied the relation between level of these factors with severity and outcome of the disease. Results Mean CRP level, creatinine, hemoglobin, and the leukocytes count in the critically ill patients were significantly higher than those of the other groups (non-critical patients); mean CRP = 54.81 mg/l, mean creatinine = 86.82 μmol/l, mean hemoglobin = 144.05 g/l, and mean leukocyte count = 7.41 × 109. The lymphocyte count was higher in patients with mild/moderate disease (mean: 1.32 × 109) and in the invasive ventilation group (mean value of 0.72 × 109), but it was considerably lower than those of the other two groups. The results showed that the platelet count was higher in critically ill patients (mean value of 205.96 × 109). However, the amount was lower in the invasive ventilation group compared with the other groups (mean level = 185.67 × 109). Conclusion With increasing disease severity, the leukocyte count and the level of CRP increase significantly and the lymphocyte count decreases. There seems to be a significant relation between platelet level, hemoglobin, and creatinine level with severity of the disease. However, more studies are required to confirm this.